The Pengaruh Ukuran Perusahaan, Arus Kas Bebas, Leverage, dan Profitabilitas Terhadap Manajemen Laba - Afifah Fadhilah; Andi Kartika (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this research is find out how the influence of firm size, free cash flow, leverage, and profitability on earnings management. The population used in this study uses hotel, tourism, and restaurant sub-sector service companies listed on the Indonesia Stock Exchange (IDX) in 2013-2020. The test results show that firm size and profitability have a positive effect on earnings management, this indicates that the larger the firm size and the level of profit, the greater the opportunity for management to practice earnings management. Free Cash Flow has a negative effect on earnings management, this shows that if the amount of free cash flow is low in a company, the higher earnings management practices will be. Leverage has no effect on earnings management, this shows that the level of leverage does not make management perform earnings management.